Financial Analysis of Operating a Resident Aesthetic Clinic. Issue 2 (15th June 2021) - Wagner, Ryan D.; Raj, Sarth; Davis, Matthew J.; Bush, Matthew; Perdanasari, Aurelia Trisliana; Izaddoost, Shayan A.; Reece, Edward M.; Winocour, Sebastian
Abstract : Background: Recent changes to the plastic surgery residency training requirements along with a general call for expanded education in cosmetic surgery have encouraged many institutions to incorporate resident aesthetic clinics into their curricula. Although the safety and satisfaction rates of resident aesthetic clinics have been well-studied, their financial viability has not. This study reviews the financial viability of the resident aesthetic clinic at the authors' institution through a cost analysis. Methods: Billing data were analyzed for all patient visits to the resident aesthetic clinic of the authors' institution during calendar year 2018. Data were extracted, including type and anatomical location of each procedure, charges collected, and supplies used. A financial analysis was performed based on fixed and variable costs and gross revenue. Results: A total of 100 unique patients were seen in the clinic over a 1-year period, resulting in 53 operations. This included 15 face, four breast, and 34 body contouring procedures. In addition, 160 cosmetic injections were performed. The gross revenue was $69, 955 and the net revenue was $36, 600. Conclusions: The resident aesthetic clinic at the authors' institution proved to be financially viable. The authors encourage other institutions to more closely examine the financial state of their resident aesthetic clinics as well. Furthermore, the authors hope that this analysis demonstrates to other programs that, with certain practice models, cost should not be a barrier to initiating and maintaining this valuable training tool.